Lack of fructose 2, 6‐bisphosphate compromises photosynthesis and growth in Arabidopsis in fluctuating environments. (March 2015) - McCormick, Alistair J.; Kruger, Nicholas J.
Summary The balance between carbon assimilation, storage and utilisation during photosynthesis is dependent on partitioning of photoassimilate between starch and sucrose, and varies in response to changes in the environment. However, the extent to which the capacity to modulate carbon partitioning rapidly through short‐term allosteric regulation may contribute to plant performance is unknown. Here we examine the physiological role of fructose 2, 6‐bisphosphate (Fru‐2, 6‐P2) during photosynthesis, growth and reproduction in Arabidopsis thaliana (L.). In leaves this signal metabolite contributes to coordination of carbon assimilation and partitioning during photosynthesis by allosterically modulating the activity of cytosolic fructose‐1, 6‐bisphosphatase. Three independent T‐DNA insertional mutant lines deficient in 6‐phosphofructo‐2‐kinase/fructose‐2, 6‐bisphosphatase (F2KP), the bifunctional enzyme responsible for both the synthesis and degradation of Fru‐2, 6‐P2, lack Fru‐2, 6‐P2. These plants have normal steady‐state rates of photosynthesis, but exhibit increased partitioning of photoassimilate into sucrose and have delayed photosynthetic induction kinetics. The F2KP‐deficient plants grow normally in constant environments, but show reduced growth and seed yields relative to wildtype plants in fluctuating light and/or temperature. We conclude that Fru‐2, 6‐P2 is required for optimum regulation of photosynthetic carbon metabolism under variable growth conditions. These analyses suggest that the capacity of Fru‐2, 6‐P2 to modulate partitioning of photoassimilate is an important determinant of growth and fitness in natural environments.